PEUTZ-JEGHERS POLYP AS A LEAD POINT FOR ILEOCOLIC INTUSSUSCEPTION IN A YOUNG MALE: A CASE REPORT - HOTA, SMRUTI RANJAN; MISHRA, PRAGNYA PARAMITA; NANDA, DEBASHIS (International Journal of Current Pharmaceutical Research, 2024)
Intussusception is defined as the invagination of one segment of the bowel into an immediately adjacent segment of the bowel. It is common in children, and idiopathic ileocolic intussusception is the most common form. It is rare in adults, and again, hamartomatous polyposis is a rare cause of intussusception in adults. But, this complication is most frequent for patients with Peutz-Jeghers syndrome (PJS). It represents 5% of all intussusceptions and accounts for only 1–5% of intestinal obstruction in adults. PJS is a clinical diagnosis based on any one of the following World Health Organization criteria: three or more histologically confirmed Peutz-Jeghers polyps; any number of PJ polyps with a family history of PJS; characteristic, prominent, mucocutaneous pigmentation with a family history of PJS; or any number of Peutz-Jeghers polyps and characteristic prominent, mucocutaneous pigmentation. Here we report a case of intussusceptions in a 21 y old male with underlying PJ polyp in the intestine and mucocutaneous pigmentation.